Biocompatibility of biodentine™ ® with periodontal ligament stem cells: In vitro study - Abuarqoub, Duaa A.; Aslam, Nazneen; Jafar, Hanan D.; Harfil, Zakariya Abu; Awidi, Abdalla S. (MDPI Multidisciplinary Digital Publishing Institute, 2020)
Biodentine™ is a tricalcium silicate-based cement material that has a great impact on different biological processes of dental stem cells, compared to other biomaterials. Therefore, we aimed to investigate the optimum biocompatible concentration of Biodentine™ with stem cells derived from periodontal ligament (hPDLSCs) by determining cell proliferation, cytotoxicity, migration, adhesion and mineralization potential. hPDLSCs were treated with Biodentine™ extract at different concentrations; 20, 2, 0.2 and 0.02 mg/mL. Cells cultured without Biodentine™ were used as a blank control. The proliferation potential of hPDLSCs was evaluated by MTT viability analysis for 6 days. Cytotoxicity assay was performed after 3 days by using AnnexinV/7AAD. Migration potential was investigated by wound healing and transwell migration assays at both cellular and molecular levels. The expression levels of chemokines CXCR4, MCP-1 and adhesion molecules FGF-2, FN, VCAM and ICAM-1 were measured by qPCR. The communication potentials of these cells were determined by adhesion assay. In addition, mineralization potential was evaluated by measuring the expression levels of osteogenic markers; ALP, OCN, OPN and Collagen type1 by qPCR. Our results showed significant increase in the proliferation of hPDLSCs at low concentrations of Biodentine™ (2, 0.2 and 0.02 mg/mL) while higher concentration (20 mg/mL) exhibited cytotoxic effect on the cells. Moreover, 2 mg/mL Biodentine™ showed a significant increase in the migration, adhesion and mineralization potentials of the derived cells among all concentrations and when compared to the blank control. Our findings suggest that 2 mg/mL of Biodentine™ is the most biocompatible concentration with hPDLSCs, showing a high stimulatory effect on the biological processes.
Keywords: Biocompatibility; Biodentine™; hPDLSCs; Stem Cells